2013
DOI: 10.4172/2155-6113.s3-006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Co-Infection is Associated with Poorer Survival of HIV-Infected Patients on Highly Active Antiretroviral Therapy in West Africa

Abstract: Background Hepatitis B has been reported to be high in HIV-infected African populations. However, the impact of this co-infection on the survival of HIV-infected Africans on long-term highly active antiretroviral therapy (HAART) remains poorly characterised. We investigated the impact of HBV/HIV co-infection on survival of HIV infected patients undergoing antiretroviral therapy in a West African population. Methods This was a clinic-based cohort study of HIV-infected adults enrolled in Nigeria, West Africa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
2
5
1
1
Order By: Relevance
“…CHB has been reported to increase mortality among HIV‐coinfected populations in Europe and North America. However, there is uncertainty regarding the mortality effect of CHB among patients on ART in Africa . Our finding of increased mortality with CHB is consistent with some prior studies from low‐ and middle‐income countries (LMICs) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CHB has been reported to increase mortality among HIV‐coinfected populations in Europe and North America. However, there is uncertainty regarding the mortality effect of CHB among patients on ART in Africa . Our finding of increased mortality with CHB is consistent with some prior studies from low‐ and middle‐income countries (LMICs) .…”
Section: Discussionsupporting
confidence: 88%
“…However, there is uncertainty regarding the mortality effect of CHB among patients on ART in Africa [14][15][16][17]. Our finding of increased mortality with CHB is consistent with some prior studies from low-and middle-income countries (LMICs) [14,15,17]. Notably, our study provides additional insight because we were able to stratify by HBV DNA level.…”
Section: Discussionsupporting
confidence: 87%
“…Hepatitis B or hepatitis C co-infection with tuberculosis increase the risk of treatment failure [19] activates latent tuberculosis [20][21][22], increase the risk of mortality [23], and drug-induced liver injury [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“… 13 A recent large study in Nigeria demonstrated that HBV co-infection is associated with a significant decrease in survival, compared to HBV-negative HIV-infected individuals, a trend that can be counteracted through the use of tenofovir-containing HAART. 14 The larger sample size involved favours this study over the conflicting evidence found in previous smaller studies in the developing world, with both positive and negative findings acquired. 13 However, more investigation into the link between HIV, viral hepatitis and HCC is required.…”
Section: The Situation In West Africamentioning
confidence: 68%